Muttukkaḷ pattu - Tilakavati (Amrutā, 2007)
Collection of short stories on social themes. - Selected short stories of Tamil writer Ti. Jāṉakirāman
Short stories. - In Tamil-Schr
Keywords: Short stories; Tamil